The Taxonomy Mobile Learning Applications in Higher Institutions of Learning in Ugandan Universities: A Case of Kabale University, Uganda. - Muhaise, Hussein; Businge,Phelix Mbabazi; Ssemaluulu, Paul; Muhoza, Gloria (Kabale University, 2024)
Since the use of mobile devices outpaces that of laptops and desktop computers today, the usability of these mobile devices is an important consideration. When mobile learning (a new kind of electronic learning) takes shape, bringing an important feature of mobility, the trend expands deeper into teaching and learning. Usability describes the quality characteristics of software product usage; hence, usability testing is a crucial concern in developing companies for the success of product deployment and use. The vast majority of existing usability evaluation approaches were created for desktop software development. As a result, currently, existing models do not specifically address mobile learning, presenting a gap that we aimed to remedy. The study developed a model that estimates usability as a function of aggregated usability influencing factors. To provide a more comprehensive model, the proposed model includes essential features from other accessible models and incorporates the majority of those that assist mobile learning. A mobile learning prototype application was designed, tested, and installed to evaluate the efficiency of the developed model, coupled with a task list for objective research. Using a sophisticated statistical technique, the feedback from the experiment and survey was then utilized to assess and validate the prototype application in terms of high, average, or low usability. The findings act as guides for eLearning-developing businesses to create more relevant mobile learning applications with high levels of usability.